Correlation between awareness of community pharmacists in Bataan of their dispensing roles and their dispensing service - Nuevas, Jan Patrice L.; Tamayo, Louise Joy N.,​​; Yu, Kathleen Michelle T.; Robles, Yolanda R.,​​ (​​​​​​​​​​Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2017)
The role of pharmacists worldwide is continually evolving in terms of scope and complexity. However, dispensing remains to be the core function of pharmacists. In 2015, the Philippine Pharmacists Association, Incorporated developed a manual called the Philippine Practice Standards for Pharmacists (PhilPSP) which contains the minimum standards required of a practicing Filipino pharmacist. Awareness of pharmacists of the dispensing roles provided in the PhilPSP manual is vital in the provision of service to patients or clients. Furthermore, understanding how pharmacists perceive their performance in dispensing service facilitates the determination of strategies that will improve the quality of such service.
The main objective of the study is to determine the correlation between the awareness of pharmacists of the dispensing roles provided in the PhilPSP and their perceived dispensing service performance. A total of 42 community pharmacists from eight municipalities in Bataan participated in the study, the sample size was arrived at using purposive and snowball sampling techniques. Questionnaires based on the PhilPSP were utilized to gather data from the respondents. It was found that respondents had generally high awareness of the dispensing roles, but had varying levels of perception on their dispensing service performance. Performance criteria that were rated high pertain to implementing good dispensing practices, undertaking prescription validation and assessment, filling of prescriptions accurately, and displaying appropriate care when dispensing. The study also revealed that clients or patients generally had high satisfaction with the service they receive from the pharmacists. A moderately high correlation was computed between awareness and perceived dispensing service (r=0.446, p value=0.003). With the data collected in the study, the awareness as well as the responsiveness of community pharmacists in Bataan of the advancements in the pharmacy practice was evaluated in preparation for the full implementation of the PhilPSP standard guidelines.
Available to the general public.
​​​​​​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2017.
Keywords: Pharmacy--Practice.; Pharmacists